Sustainable manganese catalysis for late-stage C–H functionalization of bioactive structural motifs - Son, Jongwoo (Beilstein Journal of Organic Chemistry, 2021)
The late-stage C–H functionalization of bioactive structural motifs is a powerful synthetic strategy for accessing advanced agrochemicals, bioimaging materials, and drug candidates, among other complex molecules. While traditional late-stage diversification relies on the use of precious transition metals, the utilization of 3d transition metals is an emerging approach in organic synthesis. Among the 3d metals, manganese catalysts have gained increasing attention for late-stage diversification due to the sustainability, cost-effectiveness, ease of operation, and reduced toxicity. Herein, we summarize recent manganese-catalyzed late-stage C–H functionalization reactions of biologically active small molecules and complex peptides.
Keywords: bioactive molecules; 3d transition metals; late-stage functionalization; manganese catalyst; sustainable catalysis

(untitled) - Bruce, M. I.; Iqbal, M. Z.; Stone, F. G. A. (J. Chem. Soc. A, 1970)

(untitled) - Carney, J. R.; Dillon, B. R.; Thomas, S. P. (Eur. J. Org. Chem., 2016)

(untitled) - Cano, R.; Mackey, K.; McGlacken, G. P. (Catal. Sci. Technol., 2018)

(untitled) - Hu, Y.; Zhou, B.; Wang, C. (Acc. Chem. Res., 2018)

(untitled) - Gandeepan, P.; Müller, T.; Zell, D.; Cera, G.; Warratz, S.; Ackermann, L. (Chem. Rev., 2019)

(untitled) - Aneeja, T.; Neetha, M.; Afsina, C. M. A.; Anilkumar, G. (Catal. Sci. Technol., 2021)

(untitled) - Lu, X.; He, S.-J.; Cheng, W.-M.; Shi, J. (Chin. Chem. Lett., 2018)

(untitled) - Wang, W.; Lorion, M. M.; Shah, J.; Kapdi, A. R.; Ackermann, L. (Angew. Chem., Int. Ed., 2018)

(untitled) - White, M. C.; Zhao, J. (J. Am. Chem. Soc., 2018)

(untitled) - Abrams, D. J.; Provencher, P. A.; Sorensen, E. J. (Chem. Soc. Rev., 2018)

(untitled) - Baudoin, O. (Angew. Chem., Int. Ed., 2020)

(untitled) - Kelly, C. B.; Padilla-Salinas, R. (Chem. Sci., 2020)

(untitled) - Wu, J. (Tetrahedron Lett., 2014)

(untitled) - Yang, X.; Wu, T.; Phipps, R. J.; Toste, F. D. (Chem. Rev., 2015)

(untitled) - Li, X.; Shi, X.; Li, X.; Shi, D. (Beilstein J. Org. Chem., 2019)

(untitled) - Szpera, R.; Moseley, D. F. J.; Smith, L. B.; Sterling, A. J.; Gouverneur, V. (Angew. Chem., Int. Ed., 2019)

(untitled) - Gillis, E. P.; Eastman, K. J.; Hill, M. D.; Donnelly, D. J.; Meanwell, N. A. (J. Med. Chem., 2015)

(untitled) - Wang, J.; Sánchez-Roselló, M.; Aceña, J. L.; del Pozo, C.; Sorochinsky, A. E.; Fustero, S.; Soloshonok, V. A.; Liu, H. (Chem. Rev., 2014)

(untitled) - Purser, S.; Moore, P. R.; Swallow, S.; Gouverneur, V. (Chem. Soc. Rev., 2008)

(untitled) - Smart, B. E. (J. Fluorine Chem., 2001)

(untitled) - Meanwell, N. A. (J. Med. Chem., 2018)

(untitled) - Liu, W.; Huang, X.; Cheng, M.-J.; Nielsen, R. J.; Goddard, W. A.; Groves, J. T. (Science, 2012)

(untitled) - Oh, S.; Jeong, I. H.; Shin, W.-S.; Wang, Q.; Lee, S. (Bioorg. Med. Chem. Lett., 2006)

(untitled) - Liu, W.; Groves, J. T. (J. Am. Chem. Soc., 2010)

(untitled) - Huang, X.; Liu, W.; Ren, H.; Neelamegam, R.; Hooker, J. M.; Groves, J. T. (J. Am. Chem. Soc., 2014)

(untitled) - Miller, P. W.; Long, N. J.; Vilar, R.; Gee, A. D. (Angew. Chem., Int. Ed., 2008)

(untitled) - Tredwell, M.; Gouverneur, V. (Angew. Chem., Int. Ed., 2012)

(untitled) - Jacobson, O.; Kiesewetter, D. O.; Chen, X. (Bioconjugate Chem., 2015)

(untitled) - Preshlock, S.; Tredwell, M.; Gouverneur, V. (Chem. Rev., 2016)

(untitled) - Kolb, H. C.; Finn, M. G.; Sharpless, K. B. (Angew. Chem., Int. Ed., 2001)

(untitled) - Moses, J. E.; Moorhouse, A. D. (Chem. Soc. Rev., 2007)

(untitled) - Hein, C. D.; Liu, X.-M.; Wang, D. (Pharm. Res., 2008)

(untitled) - Jewett, J. C.; Bertozzi, C. R. (Chem. Soc. Rev., 2010)

(untitled) - Liang, L.; Astruc, D. (Coord. Chem. Rev., 2011)

(untitled) - Thirumurugan, P.; Matosiuk, D.; Jozwiak, K. (Chem. Rev., 2013)

(untitled) - Tang, W.; Becker, M. L. (Chem. Soc. Rev., 2014)

(untitled) - Poonthiyil, V.; Lindhorst, T. K.; Golovko, V. B.; Fairbanks, A. J. (Beilstein J. Org. Chem., 2018)

(untitled) - Huang, X.; Bergsten, T. M.; Groves, J. T. (J. Am. Chem. Soc., 2015)

(untitled) - Silverman, R. B. (Angew. Chem., Int. Ed., 2008)

(untitled) - Niu, L.; Jiang, C.; Liang, Y.; Liu, D.; Bu, F.; Shi, R.; Chen, H.; Chowdhury, A. D.; Lei, A. (J. Am. Chem. Soc., 2020)

(untitled) - Wenk, G. L.; Danysz, W.; Mobley, S. L. (Eur. J. Pharmacol., Environ. Toxicol. Pharmacol. Sect., 1995)

(untitled) - Gideons, E. S.; Kavalali, E. T.; Monteggia, L. M. (Proc. Natl. Acad. Sci. U. S. A., 2014)

(untitled) - Meyer, T. H.; Samanta, R. C.; Del Vecchio, A.; Ackermann, L. (Chem. Sci., 2021)

(untitled) - Huang, X.; Zhuang, T.; Kates, P. A.; Gao, H.; Chen, X.; Groves, J. T. (J. Am. Chem. Soc., 2017)

(untitled) - Mayer, J. M. (Acc. Chem. Res., 2011)

(untitled) - Capaldo, L.; Ravelli, D. (Eur. J. Org. Chem., 2017)

(untitled) - Richter, M. F.; Drown, B. S.; Riley, A. P.; Garcia, A.; Shirai, T.; Svec, R. L.; Hergenrother, P. J. (Nature, 2017)

(untitled) - Campoli-Richards, D. M.; Brogden, R. N. (Drugs, 1987)

(untitled) - Park, Y.; Kim, Y.; Chang, S. (Chem. Rev., 2017)

(untitled) - Paradine, S. M.; White, M. C. (J. Am. Chem. Soc., 2012)

(untitled) - Hennessy, E. T.; Betley, T. A. (Science, 2013)

(untitled) - Paradine, S. M.; Griffin, J. R.; Zhao, J.; Petronico, A. L.; Miller, S. M.; Christina White, M. (Nat. Chem., 2015)

(untitled) - Clark, J. R.; Feng, K.; Sookezian, A.; White, M. C. (Nat. Chem., 2018)

(untitled) - Barreiro, E. J.; Kümmerle, A. E.; Fraga, C. A. M. (Chem. Rev., 2011)

(untitled) - Leung, C. S.; Leung, S. S. F.; Tirado-Rives, J.; Jorgensen, W. L. (J. Med. Chem., 2012)

(untitled) - Schönherr, H.; Cernak, T. (Angew. Chem., Int. Ed., 2013)

(untitled) - Zhu, N.; Zhao, J.; Bao, H. (Chem. Sci., 2017)

(untitled) - Friis, S. D.; Johansson, M. J.; Ackermann, L. (Nat. Chem., 2020)

(untitled) - Sato, T.; Yoshida, T.; Al Mamari, H. H.; Ilies, L.; Nakamura, E. (Org. Lett., 2017)

(untitled) - Liu, W.; Cera, G.; Oliveira, J. C. A.; Shen, Z.; Ackermann, L. (Chem. – Eur. J., 2017)

(untitled) - Feng, K.; Quevedo, R. E.; Kohrt, J. T.; Oderinde, M. S.; Reilly, U.; White, M. C. (Nature, 2020)

(untitled) - Sonogashira, K.; Tohda, Y.; Hagihara, N. (Tetrahedron Lett., 1975)

(untitled) - Caspers, L. D.; Nachtsheim, B. J. (Chem. – Asian J., 2018)

(untitled) - Ruan, Z.; Sauermann, N.; Manoni, E.; Ackermann, L. (Angew. Chem., Int. Ed., 2017)

(untitled) - Wierschke, S. G.; Chandrasekhar, J.; Jorgensen, W. L. (J. Am. Chem. Soc., 1985)

(untitled) - Gong, W.; Zhang, G.; Liu, T.; Giri, R.; Yu, J.-Q. (J. Am. Chem. Soc., 2014)

(untitled) - Vinogradova, E. V.; Zhang, C.; Spokoyny, A. M.; Pentelute, B. L.; Buchwald, S. L. (Nature, 2015)

(untitled) - Zhu, Y.; Bauer, M.; Ackermann, L. (Chem. – Eur. J., 2015)

(untitled) - Mondal, B.; Roy, B.; Kazmaier, U. (J. Org. Chem., 2016)

(untitled) - Lee, H. G.; Lautrette, G.; Pentelute, B. L.; Buchwald, S. L. (Angew. Chem., Int. Ed., 2017)

(untitled) - Liu, T.; Qiao, J. X.; Poss, M. A.; Yu, J.-Q. (Angew. Chem., Int. Ed., 2017)

(untitled) - Noisier, A. F. M.; García, J.; Ionuţ, I. A.; Albericio, F. (Angew. Chem., Int. Ed., 2017)

(untitled) - Rojas, A. J.; Zhang, C.; Vinogradova, E. V.; Buchwald, N. H.; Reilly, J.; Pentelute, B. L.; Buchwald, S. L. (Chem. Sci., 2017)

(untitled) - Tang, J.; He, Y.; Chen, H.; Sheng, W.; Wang, H. (Chem. Sci., 2017)

(untitled) - Bauer, M.; Wang, W.; Lorion, M. M.; Dong, C.; Ackermann, L. (Angew. Chem., Int. Ed., 2018)

(untitled) - Kubota, K.; Dai, P.; Pentelute, B. L.; Buchwald, S. L. (J. Am. Chem. Soc., 2018)

(untitled) - Wang, W.; Lorion, M. M.; Martinazzoli, O.; Ackermann, L. (Angew. Chem., Int. Ed., 2018)

(untitled) - Zhan, B.-B.; Li, Y.; Xu, J.-W.; Nie, X.-L.; Fan, J.; Jin, L.; Shi, B.-F. (Angew. Chem., Int. Ed., 2018)

(untitled) - Zhang, X.; Lu, G.; Sun, M.; Mahankali, M.; Ma, Y.; Zhang, M.; Hua, W.; Hu, Y.; Wang, Q.; Chen, J.; He, G.; Qi, X.; et al. (Nat. Chem., 2018)

(untitled) - Bai, Q.; Tang, J.; Wang, H. (Org. Lett., 2019)

(untitled) - Li, B.; Li, X.; Han, B.; Chen, Z.; Zhang, X.; He, G.; Chen, G. (J. Am. Chem. Soc., 2019)

(untitled) - Yuan, F.; Hou, Z.-L.; Pramanick, P. K.; Yao, B. (Org. Lett., 2019)

(untitled) - Zhan, B.-B.; Fan, J.; Jin, L.; Shi, B.-F. (ACS Catal., 2019)

(untitled) - Liu, L.; Liu, Y.-H.; Shi, B.-F. (Chem. Sci., 2020)

(untitled) - Weng, Y.; Ding, X.; Oliveira, J. C. A.; Xu, X.; Kaplaneris, N.; Zhu, M.; Chen, H.; Chen, Z.; Ackermann, L. (Chem. Sci., 2020)

(untitled) - Wu, J.; Kaplaneris, N.; Ni, S.; Kaltenhäuser, F.; Ackermann, L. (Chem. Sci., 2020)

(untitled) - Zhan, B.-B.; Jiang, M.-X.; Shi, B.-F. (Chem. Commun., 2020)

(untitled) - Key, H. M.; Miller, S. J. (J. Am. Chem. Soc., 2017)

(untitled) - Liu, J.; Liu, X.; Zhang, F.; Qu, J.; Sun, H.; Zhu, Q. (Chem. – Eur. J., 2020)

(untitled) - Peng, J.; Li, C.; Khamrakulov, M.; Wang, J.; Liu, H. (Org. Lett., 2020)

(untitled) - Wang, W.; Wu, J.; Kuniyil, R.; Kopp, A.; Lima, R. N.; Ackermann, L. (Chem, 2020)

(untitled) - Schischko, A.; Ren, H.; Kaplaneris, N.; Ackermann, L. (Angew. Chem., Int. Ed., 2017)

(untitled) - Schischko, A.; Kaplaneris, N.; Rogge, T.; Sirvinskaite, G.; Son, J.; Ackermann, L. (Nat. Commun., 2019)

(untitled) - Kaplaneris, N.; Rogge, T.; Yin, R.; Wang, H.; Sirvinskaite, G.; Ackermann, L. (Angew. Chem., Int. Ed., 2019)

(untitled) - Wang, W.; Subramanian, P.; Martinazzoli, O.; Wu, J.; Ackermann, L. (Chem. – Eur. J., 2019)

(untitled) - Zhou, B.; Chen, H.; Wang, C. (J. Am. Chem. Soc., 2013)

(untitled) - Shi, L.; Zhong, X.; She, H.; Lei, Z.; Li, F. (Chem. Commun., 2015)

(untitled) - Wang, H.; Pesciaioli, F.; Oliveira, J. C. A.; Warratz, S.; Ackermann, L. (Angew. Chem., Int. Ed., 2017)

(untitled) - Zell, D.; Dhawa, U.; Müller, V.; Bursch, M.; Grimme, S.; Ackermann, L. (ACS Catal., 2017)

(untitled) - Wang, C.; Rueping, M. (ChemCatChem, 2018)

(untitled) - Ma, X.; Dang, Y. (J. Org. Chem., 2019)

(untitled) - Cembellín, S.; Dalton, T.; Pinkert, T.; Schäfers, F.; Glorius, F. (ACS Catal., 2020)

(untitled) - Wan, S.; Luo, Z.; Xu, X.; Yu, H.; Li, J.; Pan, Y.; Zhang, X.; Xu, L.; Cao, R. (Adv. Synth. Catal., 2021)

(untitled) - Kaplaneris, N.; Kaltenhӓuser, F.; Sirvinskaite, G.; Fan, S.; De Oliveira, T.; Conradi, L.-C.; Ackermann, L. (Sci. Adv., 2021)